Yoghurt fermentation alters the composition and antiplatelet properties of milk polar lipids. (1st December 2020) - Lordan, Ronan; Vidal, Natalia P.; Huong Pham, Thu; Tsoupras, Alexandros; Thomas, Raymond H.; Zabetakis, Ioannis
Highlights: Fermentation of yoghurts from ovine milk using specific cultures altered the phospholipidome. Compositional changes increased the antithrombotic properties of polar lipids (PL) in vitro . Specific PL molecular species correlate with the antithrombotic properties against thrombin and PAF. Abstract: Dairy polar lipids (PL) seem to exhibit antiplatelet effects. However, it is not known what molecular species may be responsible. In this study, we confirmed using C30 reversed-phase (C30RP) ultra-high-performance liquid chromatography (UHPLC) coupled to high resolution accurate mass tandem mass spectrometry (HRAM-MS/MS) that fermentation of yoghurts from ovine milk using specific starter cultures altered the PL composition. These lipid alterations occurred concomitant with increased antithrombotic properties of the yoghurts PL fractions against platelet-activating factor (PAF) and thrombin-induced platelet aggregation. Specifically, elevation in phosphatidylethanolamine (PE), sphingomyelin (SM), phosphatidylcholine (PC) and their molecular species were observed following yoghurt fermentation. Furthermore, PC(18:0/18:1), PE(18:1/18:2), SM(d18:0/22:0) and several other molecular species were significantly inversely correlated with the inhibition of PAF and thrombin. These molecular species were abundant in the most bioactive yoghurts fermented by S. thermophilus and L. acidophilus, which suggest that fermentation by these microorganisms increases the antithrombotic properties of ovine milk PL.